Genomic landscape of early ecological speciation initiated by selection on nuptial colour. Issue 1 (26th August 2016) - Marques, David Alexander; Lucek, Kay; Haesler, Marcel Philipp; Feller, Anna Fiona; Meier, Joana Isabel; Wagner, Catherine E.; Excoffier, Laurent; Seehausen, Ole
Abstract: Ecological speciation is the evolution of reproductive isolation as a consequence of direct divergent natural selection or ecologically mediated divergent sexual selection. While the genomic signature of the former has been extensively studied in recent years, only few examples exist for genomic differentiation where environment‐dependent sexual selection has played an important role. Here, we describe a very young (~90 years old) population of threespine sticklebacks exhibiting phenotypic and genomic differentiation between two habitats within the same pond. We show that differentiation among habitats is limited to male throat colour and nest type, traits known to be subject to sexual selection. Divergence in these traits mirrors divergence in much older benthic and limnetic stickleback species pairs from North American west coast lakes, which also occur in sympatry but are strongly reproductively isolated from each other. We demonstrate that in our population, differences in throat colour and breeding have been stable over a decade, but in contrast to North American benthic and limnetic stickleback species, these mating trait differences are not accompanied by divergence in morphology related to feeding, predator defence or swimming performance. Using genomewide SNP data, we find multiple genomic islands with moderate differentiation spread across several chromosomes, whereas the rest of the genome is undifferentiated. The islands contain potential candidate genes involved in visual perception of colour. Our results suggest that phenotypic and multichromosome genomic divergence of these morphs was driven by environment‐dependent sexual selection, demonstrating incipient speciation after only a few decades of divergence in sympatry.